2011
DOI: 10.1016/j.ajpath.2011.04.028
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic Role of Cystathionine γ-Lyase/Hydrogen Sulfide in Streptozotocin-Induced Diabetes in Mice

Abstract: Reduced β-cell mass and increased activities of ATP-sensitive K(+) channels in pancreatic β cells are associated with the pathogenesis of diabetes. Cystathionine γ-lyase (CSE) is a major hydrogen sulfide (H(2)S)-producing enzyme in pancreatic β cells. Herein, we examine the effects of genetic and pharmacologic ablation of CSE on β-cell functions and their correlation with streptozotocin (STZ)-induced diabetes. Compared with wild-type mice, CSE knockout (CSE KO) mice that received STZ injections exhibited a del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 38 publications
(79 reference statements)
3
66
0
Order By: Relevance
“…Similarly, it has also been found that pancreatic CSE expression and H 2 S production are higher in Zucker diabetic fatty (ZDF) rats than in Zucker fatty and Zucker lean rats (101). Enhanced endogenous production of H 2 S in diabetes can induce apoptosis of insulin-secreting beta cells by enhancing endoplasmic reticulum (ER) stress via p38 MAPK activation and also stimulate K ATP channels in insulin-secreting cells (73)(74)(75). These results imply that H 2 S at high concentrations contributes to the pathogenesis of diabetes mellitus.…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Diseases?mentioning
confidence: 66%
See 1 more Smart Citation
“…Similarly, it has also been found that pancreatic CSE expression and H 2 S production are higher in Zucker diabetic fatty (ZDF) rats than in Zucker fatty and Zucker lean rats (101). Enhanced endogenous production of H 2 S in diabetes can induce apoptosis of insulin-secreting beta cells by enhancing endoplasmic reticulum (ER) stress via p38 MAPK activation and also stimulate K ATP channels in insulin-secreting cells (73)(74)(75). These results imply that H 2 S at high concentrations contributes to the pathogenesis of diabetes mellitus.…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Diseases?mentioning
confidence: 66%
“…The pathogenesis of diabetes is associated with decreased functional beta cell mass and increased activities of K ATP channels in pancreatic beta cells (99,100). It has been reported that in streptozotocin-induced diabetes in mice, pancreatic H 2 S production and CSE activity are significantly upregulated (73,76). Similarly, it has also been found that pancreatic CSE expression and H 2 S production are higher in Zucker diabetic fatty (ZDF) rats than in Zucker fatty and Zucker lean rats (101).…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Diseases?mentioning
confidence: 82%
“…Additionally, H 2 S is not beneficial in all models of renal injury as its effect can vary with the context (70). Whereas H 2 S ameliorates renin-induced hypertension (71), ischemia-reperfusion injury in the kidney and heart (17,20), obstructive kidney injury (72), preeclampsia (73), and hyperhomocysteinemia-induced chronic kidney disease (74) and protects endothelium against high glucose (75), it assumes a pathologic role as a mediator in cisplatinum-induced kidney cell injury (76), streptozotocin-induced pancreatic ␤ cell injury (77), and colon carcinoma (78). These considerations suggest that a critical evaluation of PDE5 inhibitors and H 2 S donors should be done in long term models of kidney injury in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…STZ-induced b cell death is attenuated in mice lacking CSE. Furthermore, NaHS significantly reduces insulin secretion and glucose tolerance but does not increase blood glucose in normoglycemic mice (99). Although intra-islet levels of H2S are increased in mice with type 1 diabetes, plasma levels of H2S are lower in mice with type 1 diabetes than in normoglycemic control mice (17).…”
Section: Type 1 Diabetesmentioning
confidence: 91%